2019
DOI: 10.3174/ajnr.a6079
|View full text |Cite
|
Sign up to set email alerts
|

Readout-Segmented Echo-Planar DWI for the Detection of Cholesteatomas: Correlation with Surgical Validation

Abstract: BACKGROUND AND PURPOSE: MR imaging has become an important tool for the detection of cholesteatomas of the middle ear. Various diffusion-weighted imaging sequences are available and have shown promising results. This study aimed to evaluate readoutsegmented echo-planar DWI for the detection of cholesteatoma and compare the results with surgical validation. MATERIALS AND METHODS: Fifty patients with chronic otitis media (24 females and 26 males; range, 12-76 years of age; mean age, 41 years) who underwent MR im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
1
22
1
Order By: Relevance
“…These are caused by field inhomogeneities and do not depend on TE. 22 We could not confirm the high sensitivity and specificity values for rsDWI reported by both Fischer et al 24 and Algin et al 21 In contrast to in our study, Algin et al used longer TEs for rsDWI (91-124 versus 66 ms). This might increase the T2 hyperintense signal of cholesteatomas, which could possibly lead to a higher detection rate.…”
Section: Discussioncontrasting
confidence: 72%
“…These are caused by field inhomogeneities and do not depend on TE. 22 We could not confirm the high sensitivity and specificity values for rsDWI reported by both Fischer et al 24 and Algin et al 21 In contrast to in our study, Algin et al used longer TEs for rsDWI (91-124 versus 66 ms). This might increase the T2 hyperintense signal of cholesteatomas, which could possibly lead to a higher detection rate.…”
Section: Discussioncontrasting
confidence: 72%
“…Diffusion‐weighted imaging (DWI) has emerged as a powerful diagnostic tool for the detection of cholesteatoma and is able to differentiate cholesteatoma from granulation tissue, scar, encephalocele, and benign fluid 1–4 . Non‐echo planar imaging (non‐EPI) DWI sequences, used because of their relative lack of susceptibility artifacts and geometric distortions near the skull base, have reported sensitivity and specificity of 91% and 96% for cholesteatoma detection, respectively 5 .…”
Section: Introductionmentioning
confidence: 99%
“…ossicular state. 6,14 Type of tympanic membrane perforation proved to be a confounding variable that affects the intraoperative ossicular status of CSOM patients. In this study, erosion of the three ossiculars (ossicular status score 4) was found to be the most common in total perforations (45%) followed by attic perforations (33).…”
Section: Characteristics Of Research Subjectsmentioning
confidence: 99%